2017
DOI: 10.4314/agrosh.v17i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cobb-Douglas and Translog frontier models in the analysis of technical efficiency in dry-season tomato production

Abstract: There has been contradiction among researchers regarding similarity or otherwise of technical efficiency estimate obtained from Cobb-Douglas and Translog frontier models. While some researchers believe that results obtained from the two functional forms, given the same data, were essentially similar, others disagreed. This study compared both functional forms to analyze technical inefficiency in dry-season tomato production in Jos-South Area of Plateau State. Data were collected from 60 dry-season tomato farme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…Cobb–Douglas and translog functions) forms arbitrarily (Greene, 2008). Literature suggests that average efficiency scores are very sensitive to the imposition of the different assumptions about both the distribution for inefficiency term and the functional forms (Umar et al , 2017; Cummins and Zi, 1998). In addition, the log transformation of both output and inputs for Cobb–Douglas or translog SFA functions would drop some observations as often the “value addition” variable includes zero value for nonpositive value addition.…”
Section: Methodsmentioning
confidence: 99%
“…Cobb–Douglas and translog functions) forms arbitrarily (Greene, 2008). Literature suggests that average efficiency scores are very sensitive to the imposition of the different assumptions about both the distribution for inefficiency term and the functional forms (Umar et al , 2017; Cummins and Zi, 1998). In addition, the log transformation of both output and inputs for Cobb–Douglas or translog SFA functions would drop some observations as often the “value addition” variable includes zero value for nonpositive value addition.…”
Section: Methodsmentioning
confidence: 99%
“…This implies significant difference in estimated efficiency scores generated from the two models. The significant difference in efficiency score estimates between the two models (68% for Cobb-Douglas and 59% for Translog) agreed with the findings of Umar et al (2017) and Thiam et al (2001). Similarly, Nyagaka et al (2009) applied Ordinary Least Square (OLS) production function and maximum likelihood estimates (MLE) of the Cobb-Douglas function in estimating the economic efficiency of potato farmers in Kenya and came up with efficiency scores that were significantly different across the two frontier models.…”
Section: Hypothesis Testingmentioning
confidence: 53%
“…However, there exist contradiction among researchers in respect of similarity or otherwise of technical efficiency estimates obtained using Cobb-Douglas and Translog frontier models. While Thiam et al (2001) and Umar et al (2017) observed that the average technical efficiency score from Cobb-Douglas function was significantly different from those of Translog function, Ahmad and Bravo-Ureta (1996) argued that there was no much difference in the results obtained from the two functional forms.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…the Cobb-Douglas production function to the data obtained from the Yearly Micro and Small Manufacturing Industry Survey (Survei IMK Tahunan), 2019 and 2020, conducted by BPS Province of Bali. This model has been widely used to measure the performance of technical efficiency on many fields, e.g.enterprises (Walujadi, 2004;Bohorquez & Esteves, 2008;Mahmood, 2008;Radam, Abu, & Abdullah, 2008;Barbera & Moores, 2013;Hartšenko & Sauga, 2013;Charoenrat, 2014;Noor & Siang, 2014;Prastiwi, Ayutyas, Ayunigtyas, & Saputri, 2017;Pinkovetskaia, 2018;Dagvadorj & Bo, 2019;Mbusya, 2019;Ouedraogo & Gansonre, 2020;Thuy, Le, Cuong, & Thi, 2020;), banks (Hasan, Kamil, Mustafa, & Baten, 2012;Hossain, Hossain, & Baten, 2016;Agustina, Sholihin, & Fithria, 2019;), agriculture (Trujillo & Iglesias, 2013;Mango, Makate, Hanyani-Mlambo, Siziba, & Lundy, 2015;Najjuma, Kavoi, & Mbeche, 2016;Umar, Girei, & Yakubu, 2017;Hakim, Haryanto, & Sari, 2020;Tenaye, 2020;Yilmaz, Gelaw, & Speelman, 2020;Vasyl'yeva, 2021), and macroeconomic indicators (Apostolov, 2016;Izgi et al, 2020). The total revenue would be modeled with the production inputs or factors relevant to the technical efficiency of the enterprise, such as fixed capital and labor.…”
Section: Introductionmentioning
confidence: 99%